Identification of the polyprotein termination site on encephalomyocarditis viral RNA. - Drake, N L (1982)
We show by sequence analysis of a 420-base-long region adjacent to the 3' polyadenylic acid of encephalomyocarditis viral RNA and by carboxy terminus analysis of protein E that the termination site of encephalomyocarditis virus polyprotein translation consists of two successive UAG codons located at positions 121 to 126 from the 3' polyadenylic acid.